Kajian Yuridis Peralihan Tanah Milik Adat melalui Pelepasan Hak dengan Ganti Rugi (PHGR) dan Pendaftarannya di Kantor Pertanahan Tapanuli Selatan - Mita Yasmina Harahap; Muhammad Yamin Lubis; Rosnidar Sembiring (Jurnal Hukum Lex Generalis, 2025)
Although customary land rights are still recognized by the Basic Agrarian Law, in practice many land offices process such land through granting rights over state land, as occurred in Pargarutan Jae, Sialagundi, and Muara Tais Villages where this normative juridical research using descriptive qualitative methods shows that unregistered community land is categorized as state land by the South Tapanuli Regency Land Office, resulting in land rights transfer being conducted through the PHGR mechanism despite the fact that it should be processed through sale and purchase deeds and rights conversion in accordance with applicable legal provisions. The Land Office plays a role in conducting land registration through the PTSL program and socialization to provide legal certainty, but still faces obstacles of low public understanding about procedures and benefits of land certificates, thus requiring harmonization between statutory provisions and field practices so that customary land rights status remains recognized and can be registered through rights conversion mechanisms, as well as strengthening collaboration with village officials and expanding socialization to eliminate negative public perceptions regarding land registration.